Analisis Kinerja Produktivitas Badan Usaha Milik Gampong Alue Punti Kecamatan Pasie Raya Kabupaten Aceh Jaya - Mulyadi, Dedi; Fadhly, Zuhrizal (Indonesian Journal Publisher, 2023)
The purpose of this research is to determine the productivity performance analysis of Gampong Alue Punti Gampong-Owned Enterprises (BUMG), Pasie Raya District, Aceh Jaya Regency and what are the obstacles in running Alue Punti Gampong-Owned Enterprises. Gampong-Owned Enterprises is a program where all or part of the capital is provided by a gampong party founded jointly by the gampong authorities and the gampong community to improve the quality of community work and improve the welfare of the community village. This research uses qualitative methods and uses a descriptive approach. Data collection techniques use observation instruments, interviews, documentation and audio-visual material. The research results show that the obstacle faced is that providing poor seeds and feed affects the productivity performance of this business entity. However, the productivity performance of BUMG Alue Punti can be categorized as good where this BUMG has a good sales figure, namely 95,920% with a death rate below 5%, namely 4,080%, so this Business Entity has good productivity, which has a positive impact on Gampong Alue Punti.